Effect of Soil Moisture Deficit Stress on Biomass Accumulation of Four Coffee (Coffea arabica) Varieties in Zimbabwe. (2nd February 2014) - Chemura, Abel; Mahoya, Caleb; Chidoko, Pardon; Kutywayo, Dumisani
Abstract : A study was conducted to evaluate four common coffee (Coffea arabica) varieties in Zimbabwe for drought tolerance and ability to recover. The plants were subjected to drought stress for 21 and 28 days with evaluation of recovery done 14 days after interruptive irrigation. Coffee varieties were not significantly different in initial fresh and dry biomass before stressing (P > 0.05 ). CR95 had significantly accumulated more (P < 0.05 )dry root mass (0.8 g) than the rest of the varieties after 21 days of drought stress. SL28 and CR95 had an 8.3% increase in dry biomass while Cat128 did not gain any dry biomass after 21 days of drought stress. CR95 had significantly more (P < 0.05 ) total dry biomass after 21 days and 28 days of drought stress while SL28 was consistently the least in both periods. Cat129 had the highest recovery gains in dry root, dry shoot, and total dry biomass after 21 days and 28 days of drought stress. Initial root biomass was negatively correlated with changes in total fresh and dry biomass of young coffee (r > 0.60 ) after both 21 and 28 days of drought stress, indicating that root biomass may be the most important factor determining drought tolerance in coffee varieties.